Prolonged infusion causes an increase in the incidence of phlebitis in hospitalized patients: a systematic review - Muh. Ainul Falihin; Arief Bachtiar; Tri Johan Agus Yuswanto (Media Keperawatan Indonesia, 2023)
Infusion is a medical therapy carried out invasively using an effective method to supply fluids, electrolytes, nutrients, and drugs through the blood vessels. Intravenous therapy should be monitored continuously because fluid and electrolyte imbalances can endanger the patient. However, the long-term infusion can increase the occurrence of an infection in the blood vessels called phlebitis. This study literature aims to find evidence of a relationship between the duration of use of intravenous infusions and the incidence of phlebitis. The Study Literature method is a Systematic Literature Review. This Study Literature uses five research journals from the Google Scholar and PubMed databases. The analysis of 5 journals showed a relationship between the infusion length and phlebitis incidence. It is expected that the nurses on duty are expected to be able to pay attention to the time and date of the patient's intravenous infusion and replace the intravenous infusion no more than three days or 72 hours. Further researchers are expected to be able to develop this literature study using other study focuses, namely in the form of factors that can affect phlebitis and increase information, references, and insights in using Literature review as a reference for compiling the final project.